An algorithm for a positive solution of arbitrary fully fuzzy linear system - Malkawi, Ghassan; Ahmad, Nazihah; Ibrahim, Haslinda (Springer US, 2015)
This paper proposes a new computational method to obtain a positive solution for arbitrary fully fuzzy linear system (FFLS).The new method transforms the coefficients in FFLS to a one-block matrix.As a result, none of the fuzzy operations are needed.This method can provide a solution regardless of the size of a system. Some necessary theorems are proved and new numerical examples are presented to illustrate the proposed method.